CHEMICAL DESULPHURISATION OF SUB-BITUMINOUS HIGH SULPHUR INDONESIAN COAL VIA PEROXYACETIC ACID TREATMENT - M.A.M. Ishak; K. Ismail; M.A.M. Nawi; A.F. Ismail (Universitas Gadjah Mada, 2003)
The chemical desulphurisation from an Indonesian high sulphur sub-bituminous Banjarmasin Haji Ali-Aliansar coal was investigated using the peroxyacetic acid (PAA), a mild oxidising agent. A mixture of hydrogen peroxide:acetic acid (i.e. 30:70 by volume ratio with 6% of hydrogen peroxide concentration) at 50°C of reaction temperature is capable of reducing the total sulphur content in the coal from 3.46% to 1.29% by weight, corresponding to the removal of up to ca. 72% of the total sulphur; both the inorganic (mainly pyrite) and organic sulphur forms, and approximately 10 to 44% of ashes in the coal. The simultaneous removal of both inorganic and organic sulphur forms was measured with respect to reagent volume mixed ratio, reaction temperature and hydrogen peroxide concentrations. The success of desulphurisation was measured by the reduction of the total sulphur content of the desulphurised product, its S/ C atomic ratios and ash yields of the treated coal. In general, all inorganic and some of the organic sulphur could be removed from the coal using mild conditions without severely affecting the coal microstructure as observed via the Scanning Electron Microscope with Energy Dispersive X-ray (SEM-EDX) which supplied the coal sample.